Manajemen Organisasi terhadap Efektivitas Kinerja Ponkesdes - Hidayanti, Henny (Idarotuna : Journal of Administrative Science, 2023)
One of the community-based health initiatives (UKBM) that actively incorporates the community in the construction of healthcare facilities is Ponkesdes. According to evaluation data from the Kediri City Health Service (Dinkes), the Ponkesdes program encountered a number of technical difficulties and a lack of coverage of targets. Analytical descriptive research was used in the study, which was carried out in Kediri City and Bondowoso Regency. The cross-sectional approach is the methodology employed. These include organizational structure, work schedule, work program, goal setting, coaching and supervision, and evaluation, all of which are based on organizational aspects found in this research. The analysis's findings indicate that the program variable (α=0.032) and assessment variable (α=0.003) of the health center are the organizational characteristics associated with how well its performance is carried out. Meanwhile, organizational variables (α=0.517), work schedule (α=0.383), compensation system (α=0.101), goal setting (α=0.618), supervision and coaching (α=0.837), and organizational structure variables (α=0.517) are unrelated to the village health center's efficacy. This is due to the fact that, although occasionally ignoring the established organizational structure and work schedules, the Islamic boarding school officers take seriously the need to carry out the programs at the school in order to meet predetermined targets.